Analysis of the secondary structure of mitochondrial LSU rRNA of Peruvian land snails (Orthalicidae: Gastropoda) - Ramirez, Jorge (2010)
The alignment of ribosomal genes is difficult due to insertion and deletion events of nucleotides, making the alignment ambiguous. This can be overcome by using information from the secondary structure of ribosomal genes. The aim of this study was to evaluate the utility of the secondary structure in improving the alignment of the 16S rRNA gene in land snails of the family Orthalicidae. We assessed 10 Orthalicid species (five genera). Total DNA was isolated and the partial 16S rRNA gene was amplified and sequenced using internal primers. The sequences were aligned with ClustalX and manually corrected, in DCSE format, using the 16S rRNA secondary structure of Albinaria caerulea (Pulmonata: Clausiliidae). The sequences obtained ranged from 323 to 345 bp corresponding to parts of both domains IV and V of the 16S rRNA gene. The secondary structure was recovered by homology using RnaViz 2.0. Most stems are conserved, and in general the loops are more variable. The compensatory mutations in stems are related to maintenance of the structure. The absence of a bulge-stem-loop in domain V places the family Orthalicidae within the Heterobranchia.